Influence of the use of props made from used materials on the mathematics learning achievement of middle school students - Yohanes Ovaritus Jagom; Irmina Veronika Uskono (Math Didactic: Jurnal Pendidikan Matematika, 2019)
This study aimed at determining whether or not there was an influence of the use of props made from used materials on the mathematics learning achievement of middle school students. This was a quantitative research. The writer tool the eighth grade students of SMP Negeri 12 Kupang as the samples of the study. The data obtained were analyzed using the SPSS 22 program. Before testing the hypothesis, a prerequisite test was carried out that was normality test for pretest and posttest data. The result of pretest and posttest data analysis showed that the data met the testing criteria, therefore the pretest and posttest data were normally distributed. Furthermore, the hypothesis was tested using paired sample test. After analyzing the data it was found that the value was Asymp. Sing.(2-tailed) = 0.000 < 0.05 and t counted = 17.697 > 2.080 = t table which meant that Ho was rejected meanwhile Ha was accepted meaning that there was a significant influence on the use of props made from used materials towards the mathematics learning achievement of the eight grade students of SMP Negeri 12 Kupang. The results of this study indicated that used props had an influence on mathematics learning achievement